The Law of the Iterated Logarithm - Ghimire, Santosh; Thapa, Hari (Journal of Institute of Science and Technology, 2022)
The article begins first with the history and the development of the law of the iterated logarithm, abbreviated LIL. We then discuss the LIL in the context of independent random variables, dyadic martingales, lacunary trigonometric series, and harmonic functions. Finally, we derive a LIL for a sequence of dyadic martingales.